(untitled) (Journal of Pharmaceutical Negative Results, 2017)
Cardiovascular diseases (CVDs) are a leading cause ofmorbidity and mortality. Hence, effective pharmacologicalprimary prevention strategies are of considerable interest.Clinical studies of primary prevention strategies haveshown evidence of decline in cardiovascular mortality inthe western population. However, the Asian populationhas not been represented well in previous Blood Pressure(BP) and cholesterol lowering trials in primary prevention.In view of this, the results of the recently reported HeartOutcome Prevention Evaluation-3 (HOPE-3) trial, alarge multicenter international trial with over half thesubjects enrolled from Asian countries, is of particularinterest from the Asian perspective.